2011
DOI: 10.3168/jds.2010-3260
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the feed-to-buffer ratio on bacterial diversity and ruminal fermentation in single-flow continuous-culture fermenters

Abstract: Eight single-flow continuous-culture fermenters were used in a completely randomized block design with a 2 × 4 factorial arrangement of treatments to investigate the effects of the feed-to-buffer ratio (F/B) on ruminal fermentation, the diversity and community structure of bacteria, nutrient digestibility, and N metabolism. Four diets with forage-to-concentrate ratios of 70:30 or 30:70 with alfalfa or grass hay as forage were supplied to fermenters twice per day at 2 different F/B (23.5 and 35 g of DM/L). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
3
7
0
Order By: Relevance
“…Continuous culture studies have demonstrated the decline of acetate-to-propionate ratio with decreasing pH (Cerrato-Sánchez et al, 2007a,b;Cantalapiedra-Hijar et al, 2011). A constant low pH (5.8) also decreased acetate-to-propionate ratio in our laboratory previously (Qiu et al, 2004); however, their low pH treatment was much lower than the diurnal average of the present study.…”
Section: Vfasupporting
confidence: 39%
See 1 more Smart Citation
“…Continuous culture studies have demonstrated the decline of acetate-to-propionate ratio with decreasing pH (Cerrato-Sánchez et al, 2007a,b;Cantalapiedra-Hijar et al, 2011). A constant low pH (5.8) also decreased acetate-to-propionate ratio in our laboratory previously (Qiu et al, 2004); however, their low pH treatment was much lower than the diurnal average of the present study.…”
Section: Vfasupporting
confidence: 39%
“…For the LpH treatment, we added H 3 PO 4 to a concentration of 12.5 mM to decrease buffer pH to 6.4. Both buffers allowed a parallel diurnal shift in pH (see Supplemental Figure S1; https://doi.org/10.3168/ jds.2016-12332) to better reflect normal rumen function in vivo postfeeding (Cantalapiedra-Hijar et al, 2011). The CpH treatment allowed fluctuation of fermentor pH from 6.9 prefeeding to 6.3 approximately 8 h postfeeding, with a gradual return over the remaining 16 h of each experimental day.…”
Section: Experimental Designmentioning
confidence: 99%
“…Similar VFA values were found in animals and fermenters for each diet although pH values were different depending on diet in both. The lack of correlation between pH values and VFA concentration was also observed by other authors both in vitro and in vivo (Busquet et al., ; Molina‐Alcaide et al., ; Cantalapiedra‐Hijar et al., ; Romero‐Huelva et al., ). Differences in pH probably reflect non‐structural carbohydrate content (OM‐(EE+CP+NDF)) that was higher in concentrate than in feed blocks (524, 393 and 438 g/kg dry matter for concentrate, feed block I and feed block II respectively).…”
Section: Discussionsupporting
confidence: 67%
“…Some authors have reported that cellulolytic populations do not vary when pH changes are not sharp or pH values are physiological (Mackie et al 1978;Gordon and Phillips 1989;Khafipour et al 2009). Although total volatile fatty acids and pH were not measured over the adaptation period in fermenters, the results obtained in our laboratory using the same diets and in vitro system exhibited values within physiological range (pH 6.31-6.53 and total volatile fatty acids 120-125 mmol/L for diets HC and LC, respectively;Cantalapiedra-Hijar et al 2011). These results may indicate that although the pH values in the fermenter may play an important role in the in vitro fermentation profile, other in vitro-related factors such as the dilution rate (Crawford et al 1980), content stratification (Muetzel et al 2009), or the harvest and processing of fermenter inoculum (Ziemer et al 2000) are also involved in the in vivo-in vitro discrepancies.…”
Section: Ii) T-rflpmentioning
confidence: 71%